Adaptive Risk Communication System and Policy for Health Crisis in Indonesia - Choirul Fajri; Nunung Prajarto; Ana Nadhya Abrar (Universitas Muhammadiyah Yogyakarta, 2023)
Three years since its first appearance at the end of 2019, until now, Covid-19 still exists. Realizing that the handling of Covid-19 cannot be carried out alone, the Indonesian government is trying to involve various parties to provide the public with an understanding of the risks. Considering that Covid-19 is still around, efforts to reflect on the risk communication system and the various risk policies adopted are necessary as a preventive action to anticipate various potential risks and health crises in the future. This research is qualitative with a case study type. Data were obtained through in-depth interviews with the Covid-19 handling committee in Indonesia (KPC PEN), observation, and literature study. The results of this study indicate that in building a risk communication system, the government cooperates with various parties. The communication system and risk policies implemented by the Indonesian government are not optimal in understanding risks to the public. Efforts are needed to conduct regular evaluations and monitoring to optimize communication systems and risk policies in anticipation of future health crises.